PROBLEMS OF THE SCHOLARLY PUBLICATION OF VASYL STEFANYK’S BELLES-LETTRISTIC LEGACY - Піхманець, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article indicates difficulties and scientific collisions connected with the publication of Vasyl Stefanyk’s short stories and novellas.They concern working-out of scientific principles of such work, linguistic and orthographic peculiarities, selecting. Principal works, defining borders of, in fact, belles-lettristic legacy of the author of novellas, problems of textual commentary, etc. The scholar’s own view on disputable issues is expressed and the ways of their solution are outlined.